Winch and Collingwood on Logic in the Light of Published and Unpublished Material - Lagerspetz, Olli (Imprint Academic, 2023)
This essay compares R. G. Collingwood and Peter Winch regarding their views on logic. Collingwood was an important source for Winch, more so than is usually acknowledged. More importantly, they pursued parallel views on what philosophy should be. For both, the central question about logic was its status as a representation of actual thinking. Both contrasted an ‘Aristotelian’ conception of logic with a ‘Socratic’ conception. For the ‘Aristotelian’, we can identify and analyse the logical form of a proposition independently of its use. The logical form of a judgment is already ‘there’, and logic, as an academic discipline, is the study of that structure. In contrast, for both Collingwood and Winch, we can identify logical relations such as implication, consistency and contradiction only when they are embedded in a context. The ‘Socratic’ conception of logic implied, for Collingwood, studying judgments as they occur in ‘systems’ of inquiry. For Winch, the use of arguments had an ethical aspect. The dimension of superficiality and depth is significant for identifying legitimate and illegitimate inferences. ‘Meaning’ and ‘understanding’ are logical, not psychological concepts, because they themselves enter as elements of the reasoning.